2012
DOI: 10.1007/s10815-012-9739-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel protocol for isolation and purification of human granulosa cells

Abstract: A novel protocol for granulosa cell purification has been developed yielding samples that are largely free of nondesirable cells. This protocol provides a purification solution, especially for patient samples that have significant RBC contamination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 32 publications
0
10
0
3
Order By: Relevance
“…Normal granulosa cell function is therefore essential for oocyte development [ 42 ]. The in vitro culture model of pGCs purified from human follicles is widely used in reproductive research [ 43 , 44 ], but the viability and status of pGCs also gradually decreased with longer culture time; thus, it is a potential aging cell model. We found that TF3 could delay granulosa cell apoptosis in vitro and significantly reduce ROS-induced apoptosis and oxidative stress injury in the H 2 O 2 -induced oxidative stress model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Normal granulosa cell function is therefore essential for oocyte development [ 42 ]. The in vitro culture model of pGCs purified from human follicles is widely used in reproductive research [ 43 , 44 ], but the viability and status of pGCs also gradually decreased with longer culture time; thus, it is a potential aging cell model. We found that TF3 could delay granulosa cell apoptosis in vitro and significantly reduce ROS-induced apoptosis and oxidative stress injury in the H 2 O 2 -induced oxidative stress model.…”
Section: Discussionmentioning
confidence: 99%
“…Normal granulosa cell function is therefore essential for oocyte development [42]. The in vitro culture model of pGCs purified from human follicles is widely used in reproductive research [43,44], but the viability and status of pGCs also gradually decreased with longer culture time; Figure 6: TF3 may affect granulosa cell function by regulating autophagy through the mTOR pathway. pGCs were routinely cultured for 24 h and then starved in a serum-free culture medium for 24 h. TF3 (10 μM) or control treatment was given for 6 h. Cells were collected for transcriptome sequencing, and differentially expressed genes were subjected to GO analysis related to cell biological processes (a) and MCODE analysis related to signaling pathways (b).…”
Section: Discussionmentioning
confidence: 99%
“…After removing the supernatant, samples were resuspended in phosphate-buffered saline (PBS). To isolate GCs from FF, PBS-resuspended samples were run through a 50% Percoll gradient (Sigma, St. Louis, USA), followed by centrifugation at 1000 g for 20 min at 4 °C as previously described [19, 20], with minor modifications. GCs were collected from the second layer of the liquid.…”
Section: Methodsmentioning
confidence: 99%
“…Granulosa cells were isolated from both the follicular fluid aspirate and the subsequent flush of the same follicle, as previously described (Chilvers, Bodenburg, Denner, & Urban, ; Quinn et al, ). Samples were centrifuged at 2,000 g for 5 min at 4°C and the supernatant (follicular fluid or flush media) was removed.…”
Section: Methodsmentioning
confidence: 99%